Estudo de parâmetros físico-químicos da solução do poro de argamassas com adições minerais e sua contribuição para a durabilidade - Santos, Aloísio Fernando Silva (2023)
Recent studies have shown that the durability of reinforced concrete is related to its chemical ability to maintain an alkaline environment through the porous solution. In the absence of aggressive agents, the passivation film on the steel bars remains stable. However, in the presence of chlorides or under the effect of carbonation, this protection can be interrupted and the corrosion process initiated. Therefore, it is crucial to have knowledge of the internal chemical composition of the pores in cementitious materials to mitigate these effects, especially the chemical knowledge of the free water present in these materials. The chemical analysis of the electrolytic solution present in the pores has been studied for decades. However, there are few studies that focus on cementitious materials subjected to combinations of aggressive agents and the use of mineral additions. Thus, this work aims to analyze and obtain physicochemical parameters of the pore solution in mortars with silica fume and metakaolin using different methods of extracting the internal free water, namely: pressure application extraction, ex situ leaching, in situ leaching, and equilibrium water extraction when subjected to chloride attack or accelerated carbonation, as well as both situations combined. The use of mineral additions was considered with the objective of generating different chemical parameters related to the aqueous solution in the pores since they chemically modify the entire composition and also modify the microstructure of mortars. They are widely used supplementary materials of great relevance in civil construction. pH analysis, electrical conductivity, ionic strength, dissolved solids, redox potential, and ionic chemical analysis were performed. To better understand the formation and changes in the chemical composition of the pore solution, microstructural implications were also studied in terms of thermogravimetry, FTIR, XRD, SEM, surface electrical resistivity, specific surface area, and pore volume. The different analytical techniques used to analyze the ionic composition of the pore solution were considered similar and reliable. It was observed that mineral additions contributed to the reduction of the ionic charge in the solution, while carbonation and chloride attack caused significant changes in the ions present. When these mechanisms occur in combination, the order in which they occur influences the formation of products and the quality of the pore solution. Finally, it is important to emphasize that the methods of extracting the pore solution can be used in different situations, but each one has its own limitations and requires precautions during the test. It is essential to consider these restrictions and adopt appropriate measures to ensure the reliability of the obtained results.